2019
DOI: 10.3389/fmars.2019.00754
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Short Term Methylmercury Exposure on Growth and Development of the Large Yellow Croaker Embryos and Larvae

Abstract: Due to the high toxicity in aquatic food chain, the toxic effects of methylmercury (MeHg) on organisms have caused widespread concerns, but little has been reported on its effects on marine fish. The acute and sub-lethal toxicities of MeHg chloride to an important aquaculture species in southeast coast of China -large yellow croaker (Pseudosciaena crocea) embryos and larvae were investigated in this study. Acute toxicity tests showed that the 48-h LC 50 values of methylmercury to fish embryos and larvae were 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
2
0
2
Order By: Relevance
“…For example, LC50 values ranged from 42 to 75 ppb in rainbow trout and brook trout exposed for 24–96 h (Bleau et al, 1996; Canadian Council of Ministers of the Environment, 2003; Wobeser, 1975). In fathead minnow exposed for 24 h, the LC50 was 221 ppb (Devlin, 2006), and in yellow croaker exposed for 48 h, the LC50 was 28.4 ppb (Yu et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…For example, LC50 values ranged from 42 to 75 ppb in rainbow trout and brook trout exposed for 24–96 h (Bleau et al, 1996; Canadian Council of Ministers of the Environment, 2003; Wobeser, 1975). In fathead minnow exposed for 24 h, the LC50 was 221 ppb (Devlin, 2006), and in yellow croaker exposed for 48 h, the LC50 was 28.4 ppb (Yu et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In a marine flounder, Paralichthys olivaceus, morphological abnormalities and mortality of embryos significantly increased following aqueous exposure to 13 and 11 µg/L of methylmercury (48 h exposure) (Ren et al 2019). Embryos of another marine fish, Pseudoscianaena crocea, appeared to be less sensitive than the flounder with 50% lethality following 48 h exposure to aqueous methylmercury reported to be 28 µg/L (Yu et al 2019). Yu et al also reported a higher rate of morphological abnormalities at ≥1 µg/L.…”
Section: Toxicity Of Mercury To Marine Organismsmentioning
confidence: 98%
“…Иванова, Е.С., Комов, В.Т., Ельцова, Л.С., Борисов, М.Я., Тропин, Н.Я., 2020. Содержание ртути в рыбе из водоемов и водотоков Вологодской области и расчет безопасных для здоровья Yu, X., Wu, F., Xu, X., Chen, Q., Huang, L. et al, 2019…”
Section: список литературыunclassified
“…Металл проникает через эпителий органов в кровяное русло, связывается с белками плазмы и с током крови транспортируется во все ткани, где через клеточные мембраны поступает внутрь клеток . Соединения ртути вызывают замедление роста рыб, эндокринные нарушения, снижение успешности нереста, подавление иммунитета и повреждение таких органов, как печень и почки , сердечно-сосудистой системы , нервной системы , ухудшение вылупления, выживания и роста эмбрионов и личинок (Yu et al, 2019). Молекулярные механизмы негативного влияния ртути включают несколько регуляторных путей, затрагивающих энергетический обмен, окислительный стресс, апоптоз, иммунный ответ и метаболизм липидов (Немова, 2005;Yadetie et al, 2013 и др.).…”
Section: Introductionunclassified